2005
DOI: 10.1038/sj.ejcn.1602201
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vitamin supplementation to HIV-infected pregnant women on the micronutrient status of their infants

Abstract: Objective: We examined whether supplementation with vitamin A and/or vitamins B, C, and E to HIV-infected women during pregnancy and lactation is related to increased concentrations of vitamins A, B12, and E in their infants during the first 6 months of life. Design: We carried out a randomized clinical trial among 716 mother-infant pairs in Dar-es-Salaam, Tanzania. Women were randomly allocated to receive a daily oral dose of one of four regimens: vitamin A, multivitamins (B, C, and E), multivitamins includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 48 publications
(57 reference statements)
3
27
1
Order By: Relevance
“…Although additional studies of the effects of vitamin E supplementation on tocopherol concentrations in breast milk were not available for comparison, the findings from our study are consistent with those from Baylin et al (2005) who reported that MV supplementation was associated with increased serum vitamin E in breastfed infants at 6 weeks and 6 months of age and reduced serum retinol in infants at 6 weeks of age. Changes in nutrient concentrations with MV supplementation, including a decrease in retinol, might be attributed to the a-tocopherol content of the supplement.…”
Section: Discussionsupporting
confidence: 82%
“…Although additional studies of the effects of vitamin E supplementation on tocopherol concentrations in breast milk were not available for comparison, the findings from our study are consistent with those from Baylin et al (2005) who reported that MV supplementation was associated with increased serum vitamin E in breastfed infants at 6 weeks and 6 months of age and reduced serum retinol in infants at 6 weeks of age. Changes in nutrient concentrations with MV supplementation, including a decrease in retinol, might be attributed to the a-tocopherol content of the supplement.…”
Section: Discussionsupporting
confidence: 82%
“…24 In addition, improvements in the mother's immune status 13 may result in less morbidity, more energy, and ability to stimulate her child, resulting in improvements in developmental scores. In a similar way, improvement of child multivitamin status throughout the supplement period, including observed increases in serum vitamins B 12 and E in these children, 16 may also be associated with reduced morbidity, particularly among initially nutritionally deficient children, 33 and as a result affect their mental and psychomotor development. 34 Both vitamins E and C are antioxidants that are believed to enhance immune responses and phagocytosis.…”
Section: Discussionmentioning
confidence: 92%
“…14 Vitamin A supplementation during pregnancy has also been shown to reduce the risk for preterm delivery among HIV-infected women. 15 Baylin et al 16 demonstrated that vitamin A supplements that are given to HIV-infected mothers during pregnancy and lactation increases serum vitamin A in their infants during the first 6 months of life. Similarly, multivitamin supplements (B, C, and E) increase serum vitamins B 12 and E.…”
mentioning
confidence: 99%
“…Maternal nutritional status can be an important factor determining the micronutrient status of a breastfed infant (Dijkhuizen et al, 2001Baylin et al, 2005). Supplementation with micronutrients during pregnancy has the advantage of addressing the needs of both mothers and infants simultaneously.…”
Section: Introductionmentioning
confidence: 99%